ANALISIS TANGGUNG JAWAB DIREKTORAT JENDERAL HAKI TERHADAP KASUS PENDOMPLENGAN NAMA / PASSING OFF TERHADAP MEREK TERKENAL “M&G” DITINJAU DARI UNDANGUNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS (STUDI KASUS PUTUSAN NO 526K/PDT.SUS-HKI/2020) - Michael Michael; Christine S.T. Kansil (Fakultas Hukum Universitas Tarumanagara, 2021)
During the period of international trade, for global agreements that have been ratified by Indonesia, the position of brands and geographical features is very important, especially in protecting fresh business competition, protecting customers, and preventing micro, small and medium enterprises and factories in the country. Intellectual property in law is divided into 2 groups, namely the right to make (copyrights) and factory ownership rights (industrial property rights). Factory property rights include patents, business brands, and factory concepts (Industry design), Anti Fraud (ends unfair competition), structured circuit position rules and business secrets. Trademark rights are the scope of property rights, because brand rights are the right to use a logo or brand for products that are traded by one person with other people's products even though they do not have the main factor as what is meant by the interpretation of intellectual property, namely there is no intellectual effort factor in the form of inventions or findings. However, once there is a meeting between manufacturing rights, patent rights and trademark rights, it is observed from the nature or form of the rights, namely the rights to intangible goods.